PELAKSANAAN POLIGAMI DALAM HUKUM PERKAWINAN SEBAGAI HUKUM POSITIF DI INDONESIA - Abdul Hijar Anwar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The provisions for polygamy as contained in article 58 paragraph (1) meet the requirements specified in article 5 of Law no. 1 of 1974. However, Article 58 adds conditions: the wife's consent and the certainty that the husband is able to guarantee the necessities of life for his wives and their children. The wife's consent is subject to exceptions as stated in Article 58 paragraph (3) if it is impossible for the wife or wives to be asked for their consent and cannot become parties to the agreement or there is no news from them for at least two years or other reasons that have been assessed by the judge. , then polygamy can be done without the consent of the wife. Article 59 In the event that the wife does not want to give consent, and the application for permission to have more than one wife is based on one of the reasons stipulated in Article 55 paragraphs (2) and 57, the Religious Courts can determine the granting of permission after examining and hearing the wife concerned in the trial of the Religious Courts, and against this determination the wife or husband can appeal or cassation. Thus, based on the description above, we can draw the conclusion that the legal provisions in the KHI in the case of regulating polygamy are moderate, namely by not closing the door to polygamy tightly and not opening it wide. Reflection of a moderate attitude towards the legal provisions contained in the Compilation of Islamic Law (KHI), namely giving authority to polygamy cases.Keywords: Polygamy, Marriage Law, Indonesia.